Y dipion transitions at energies near the Y(4S) - Glenn, S; Kwon, Y; Lyon, A; Roberts, S; Thorndike, E; Jessop, C; Lingel, K; Marsiske, H; Perl, M; Savinov, V; Ugolini, D; Zhou, X; et al. (1999)
Using a 4.19 fb-1 data sample collected with the CLEO II detector at the Cornell Electron Storage Ring, we have searched for dipion transitions between pairs of Y resonances at center of mass energies Ec.m. = 10.58 GeV and Ec.m. = 10.52GeV. We obtain the 90% confidence level upper limits B(Y(4S) →Y(2S)π+π-)<3.9×10-4 and B(Y(4S)→Y(1S)π+π-)<1.2×10 -4. We also observe the transitions Y(3S)→Y(1S)π+π-, Y(3S)→Y(2S)π+π-, and Y(2S)→Y(1S)π+π-, from which we measure the cross sections for the radiative processes e+e-→Y(3S)γ and e+e-→Y(2S)γ. We obtain σee→Y(3S)γ = (17.8±3.0±1.7) pb and σee→Y(2S)γ=(15.5±1.3±1.4) pb at Ec.m. = 10.58 GeV, and σee→Y(3S)γ=(27.3±5.0±2.6) pb and σee→Y(2S)γ=(16.3±1.8±1.5) pb at Ec.m. = 10.52 GeV, which we compare with theoretical predictions. ©1999 The American Physical Society.